The First epistle general of Peter - Stibbs, Alan M. (Alan Marshall); Walls, Andrew F. (Andrew Finlay) (Grand Rapids, Michigan : Wm. B. Eerdmans Publishing Company, 1959)
1 Peter has a message for Christians of every time and place. Its three main themes are particularly relevant to the present day. When scientific achievement, the welfare state, and dialectical materialism combine to make our century too worldly-minded, 1 Peter recalls us to the heavenly and eternal outlook, and reminds us we are but strangers and pilgrims here. Similarly, when relief from physical disease and the provision of physical comfort tend to be treated as the primary Christian objectives, we need the reminder that holiness matters more, and that all who would follow Christ must be prepared to suffer for righteousness' sake, and to recognize that God uses suffering for the highest good. Also, when moral standards tend to decline, and when young converts are tempted to spend their enthusiasm more in words than in deeds, we need the challenge to express our response to the gospel in transformed behavior in relation to our fellow men. - Back cover.
Includes bibliographical references.
Keywords: Bible. -- Commentaries; Commentaries